INCONSISTENT VAR REGRESSION WITH COMMON EXPLOSIVE ROOTS. (16th January 2013) - Phillips, Peter C.B.; Magdalinos, Tassos
Abstract : Nielsen (Working paper, University of Oxford, 2009) shows that vector autoregression is inconsistent when there are common explosive roots with geometric multiplicity greater than unity. This paper discusses that result, provides a coexplosive system extension and an illustrative example that helps to explain the finding, gives a consistent instrumental variable procedure, and reports some simulations. Some exact limit distribution theory is derived and a useful new reverse martingale central limit theorem is proved.